2018
DOI: 10.1093/jxb/ery308
|View full text |Cite
|
Sign up to set email alerts
|

Environmental triggers for photosynthetic protein turnover determine the optimal nitrogen distribution and partitioning in the canopy

Abstract: Plants acclimatize their photosynthetic functions in leaves constantly to the fluctuating light, thereby optimizing the use of photosynthetic nitrogen (Nph) at the canopy level. To investigate the complex interplay between external signals during the acclimation processes, a mechanistic model based on the concept of protein turnover (synthesis and degradation) was proposed and parameterized using cucumber grown under nine combinations of nitrogen and light in growth chambers. Integrating this dynamic model int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
0
15
1
Order By: Relevance
“…Nevertheless, these data are in contrast to a modeling study by Retkute et al (2015) which indicated that the optimal plant response to fluctuating irradiance was to increase A max . These results may also be in disagreement with a recent commentary by Pao et al (2019b), who suggested that photosynthetic capacity (expressed as maximum electron transport and carboxylation rates, J max and V cmax , respectively) is reduced in leaves under fluctuating irradiance; this analysis was based on a non-linear relationship between irradiance and protein synthesis rate, using data from a previous modeling study validated with measurements on Cucumis sativa (grown under constant irradiance) as reference (Pao et al, 2019a). The reasoning by Pao et al (2019b) is that leaves under fluctuating irradiance experience a relatively longer time close to the saturating end of this relationship compared to leaves under lower, uniform light.…”
Section: Summary Of Observed Responses To Fluctuating Irradiancecontrasting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, these data are in contrast to a modeling study by Retkute et al (2015) which indicated that the optimal plant response to fluctuating irradiance was to increase A max . These results may also be in disagreement with a recent commentary by Pao et al (2019b), who suggested that photosynthetic capacity (expressed as maximum electron transport and carboxylation rates, J max and V cmax , respectively) is reduced in leaves under fluctuating irradiance; this analysis was based on a non-linear relationship between irradiance and protein synthesis rate, using data from a previous modeling study validated with measurements on Cucumis sativa (grown under constant irradiance) as reference (Pao et al, 2019a). The reasoning by Pao et al (2019b) is that leaves under fluctuating irradiance experience a relatively longer time close to the saturating end of this relationship compared to leaves under lower, uniform light.…”
Section: Summary Of Observed Responses To Fluctuating Irradiancecontrasting
confidence: 83%
“…This equilibrium state would depend on the speed of dynamic acclimation and the degree of linearity in the response of plant traits to changes in irradiance. These dynamics have been captured in simulation models either (i) by implementing a goalseeking behavior that calculates steady-state acclimation from optimization theory (Yin et al, 2019) or (ii) by simulating protein turnover dynamically (Thornley, 1998;Kull and Kruijt, 1999;Barillot et al, 2016;Pao et al, 2019a). Experimental evidence exists that coordination across leaves may be achieved through cytokinins carried by the transpiration stream (Pons et al, 2001), as transpiration will vary according to the irradiance profile.…”
Section: Dynamic Acclimation May Never Reach a Steady Statementioning
confidence: 99%
“…to control plants in order to normalize for the effects of leaf age [18]. Cucumber has a high leaf turnover rate (the biochemical capacity for photosynthesis drops by 50% after 15 days past full expansion of the leaf [11,34,35]) and the accumulation of salt to a toxic level takes 15-20 days [11]. Without this normalization the ionic effects would be overestimated.…”
Section: Pumpkin Improved Photosynthesis and Regulated Ion Distributimentioning
confidence: 99%
“…Protein abundance is regulated by the orchestration of multiple mechanisms and is the outcome of protein turnover: the continuous dynamics of protein synthesis and degradation (Kristensen et al , 2013; Nelson and Millar, 2015). Based on the concept of protein turnover, we have recently presented a mechanistic model describing photosynthetic acclimation (Pao et al , 2019) in which the experimental data suggested a non-linear relationship between the PPSR and PAR (see Supplementary Fig. S1 at JXB online).…”
mentioning
confidence: 99%
“…1A), it is possible to assess the differences in photosynthetic protein abundance between plants grown under FL and SQ. To simulate the effect of the diurnal light fluctuation, we first converted the parameters in the model of Pao et al (2019) to an hourly basis by assuming a 12 h photoperiod and zero protein synthesis in the dark. Then, three FL patterns (Fig.…”
mentioning
confidence: 99%